Formative Assessment in China and Finland : Teachers’ perception, attitude and implementation - Peng, Qian (fi=Turun yliopisto|en=University of Turku|, 2017)
Formative Assessment (FA) has been introduced to China for more than ten years. Both the educators and administrators realized the importance of it. However, the implementation of FA is not sufficient and effective in China. In 1970s, FA was brought in to Finland. And the assessment reform in Finland succeeded. In this paper, we try to find out how the teachers from these two countries conduct FA by comparing teachers’ perception, attitude and implementation in two different educational contexts, China and Finland. 59 teachers from Finland and China participated in this survey and answered the questionnaire. The results show that Finnish teachers stress students’ autonomy in FA, give more trust to students and have more confidence in students’ learning ability. Chinese teachers emphasize the FA positive effect on learning and teaching.